Learning Maf'ul Muthlaq With Arabic Poetry Writing Strategies To Improve Students' Creative Thinking Skills - Alfan, Muhammad; Khasairi, Moh.; Ridwan, Nur Anisah; Ma’sum, Ali; Saifullah, Mochammad; Muthmainnah, Fathimah (Ijaz Arabi Journal of Arabic Learning, 2023)
This study is motivated by the low creative thinking skills of students in applying the grammatical rules of Maf’ul Muthlaq in writing and speaking in Arabic and their low cognitive skills in understanding Maf’ul Muthlaq learning materials. These deficiencies result from the application of grammar teaching strategies limited to giving lectures, explanations, presentations, and examples. None of them allows students to think creatively, which leads to high cognitive skills. This fact is based on the experience of the researchers in teaching Arabic grammar and writing skills courses. This study aims to apply the poem-writing strategy using Canva in the Tathbiq Nahwi Tsanawi course and assess its effectiveness in increasing students' creative thinking skills in using Maf’ul Muthlaq. This study utilizes an experimental method with the one-shot case study design to assess the effectiveness of this strategy in improving the students' creative thinking skills. The results of this study indicate that the implementation of the poem-writing strategy using Canva can improve the students' creative thinking skills in learning Maf’ul Muthlaq to a high level.